UTILIZATION AND ENGINEERING OF PISTON WASTE BY SHOT PEENING METHOD AS ALTERNATIVE MATERIAL FOR FISHING VESSEL PROPELLERS - Priyambodo, Bambang Hari; Yaqin, Rizqi ilmal; Fattah, Rauuf Nur; Slamet, Sugeng (Politeknik Kelautan dan Perikanan Dumai, 2024)
This study aims to evaluate the utilization of used piston waste as an alternative material for making fishing boat propellers. Engineering is carried out to improve its mechanical properties by shot peening treatment. Shot peening is a surface treatment method by shooting small steel ball particles in a controlled manner. In this study, used pistons were recycled and used as the basic material for propellers, then shot peening was carried out with a pressure of 8 bar with variations in shooting duration for 5, 10, 15, and 20 minutes. Testing includes testing the chemical composition of the specimen, tensile testing, and observing the micro structure. Tensile testing is to determine mechanical strength, while macro photography is to identify changes in surface structure. The results of the chemical composition test state that the recycled piston is AL-Si-Cu. Meanwhile, the results of the tensile test show that the longer the shot peening duration, the tensile strength of the material increases significantly. Shot peening with a duration of 20 minutes gives the highest strength. The increase in tensile strength is 43% or 113 MPa compared to the non-treatment specimen. Micro structure observations show that the shot peening process creates a denser surface layer, so that tensile strength can be increased. This research is expected to be a reference for the propeller industry to increase production efficiency and sustainability.